Technique to Assess and Improve Refinery Performance: Assessing and Improving Refinery Performance in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Startingwith the first refinery built in Margherata in 1883 and subsequently relocatedin Digboi in 1901, India today has refineries at 14 locations with a totoalrefining capacity of 60.55 million tonnes per annum (MMTPA). While severalrevamps/energy efficiency measures have been carried out in each of theserefineries, it is worth noting that most of the refineries in India weredesigned in the 1970's or earlier when there was no energy crisis.